Immunostimulatory nanoparticles delivering cytokines as a novel cancer nanoadjuvant to empower glioblastoma immunotherapy - Flávia Sousa; Henry Lee; Mauro Almeida; Amelie Bazzoni; Barbara Rothen-Rutishauser; Alke Petri-Fink (Drug Delivery and Translational Research, 2024)
Glioblastoma (GBM) stands as a highly aggressive and deadly malignant primary brain tumor with a median survival time of under 15 months upon disease diagnosis. While immunotherapies have shown promising results in solid cancers, brain cancers are still unresponsive to immunotherapy due to immunological dysfunction and the presence of a blood–brain barrier. Interleukin-12 (IL-12) emerges as a potent cytokine in fostering anti-tumor immunity by triggering interferon-gamma production in T and natural killer cells and changing macrophages to a tumoricidal phenotype. However, systemic administration of IL-12 toxicity in clinical trials often leads to significant toxicity, posing a critical hurdle. To overcome this major drawback, we have formulated a novel nanoadjuvant composed of immunostimulatory nanoparticles (ISN) loaded with IL-12 to decrease IL-12 toxicity and enhance the immune response by macrophages and GBM cancer cells. Our in vitro results reveal that ISN substantially increase the production of pro-inflammatory cytokines in GBM cancer cells (e.g. 2.6 × increase in IL-8 expression compared to free IL-12) and macrophages (e.g. 2 × increase in TNF-α expression and 6 × increase in IL-6 expression compared to the free IL-12). These findings suggest a potential modulation of the tumor microenvironment. Additionally, our study demonstrates the effective intracellular delivery of IL-12 by ISN, triggering alterations in the levels of pro-inflammatory cytokines at both transcriptional and protein expression levels. These results highlight the promise of the nanoadjuvant as a prospective platform for resharing the GBM microenvironment and empowering immunotherapy. Graphical Abstract

Detection of submicron- and nanoplastics spiked in environmental fresh- and saltwater with Raman spectroscopy - Jessica Caldwell; Laura Rodriguez-Lorenzo; Begoña Espiña; Aaron Beck; Friederike Stock; Kathrin Voges; Katsia Pabortsava; Christopher Feltham; Alice Horton; Richard Lampitt; Barbara Rothen-Rutishauser; Patricia Taladriz-Blanco; et al. (Marine Pollution Bulletin, 2024)